ROLE OF EXTENDER ADDITIVES AND AI TECHNICIANS IN IMPROVING FIRST SERVICE CONCEPTION RATE WITH FROZEN SEMEN IN CATTLE AND BUFFALOES UNDER FIELD CONDITIONS - DHAMI, A J; CHATURVEDI, DEVANGANA; THESIA, M J; CHAUDHARI, D V; PATEL, B S (The Indian Journal of Animal Reproduction, 2023)
This study involved semen ejaculates with >75 % initial motility of 3 Gir and 3 Murrah bulls split-diluted at 100 million sperm per ml using Tris-citric acid-fructose-egg yolk-glycerol (TFYG) extender without (control) and with fortification of additives Mifepristone (10 μg/ml), Sericin (5 mg/ml) and Taurine (4 mg/ml) and frozen in French mini straws using a programmable biofreezer. The straws were thawed in water bath at 37°C for 30 sec. The frozen semen doses of buffalo (1446) and cattle (495) so prepared were distributed among 18 good to average performing AI technicians of Panchamahals District Cooperative Milk Producers Union Limited, Godhara (Gujarat). Irrespective of additives, the overall first AI conception rate, and the mean post-thaw percent sperm progressive motility, viability, HOS reactivity, CTC assay (non-capacitated sperm, ‘F’ pattern) and CASA traits, viz., VAP (μm/s), VCL (μm/s), (VSL (μm/s) and ALH (μm) recorded in Gir bull semen were 47.07, 46.73±0.67, 63.99±0.83, 54.36±0.78, 65.56±0.95, 30.89±0.63, 73.68±1.03, 23.98±0.65 and 1.86±0.04, respectively. The corresponding figures for Murrah bull semen were 50.76, 48.81±0.82, 65.63±0.70, 56.64±0.64, 68.80±0.82, 33.35±0.72, 72.26±0.83, 27.29±0.83 and 1.90±0.04. All values where apparently or statistically better in Murrah than Gir bull semen. The effect of extender-additives was highly significant (p<0.01) on all the parameters studied in both the species. The percent motile, live, HOS reactive and non-capacitated sperm, and conception rates were significantly (p<0.01) higher in semen extender supplemented with Mifepristone than in control extender, and the values for Sericin and Taurine fortified TFYG were intermediary in both the species. However there was no effect of additives on CASA traits in either of the species. The first AI conception rates among 12 technicians involved for buffalo insemination ranged from 44.08 to 56.52% (p<0.01), and among 6 technicians involved for crossbred cattle insemination with Gir bull semen ranged from 40.37 to 54.88% (p<0.05). There was positive association of sperm quality parameters and fertility in both the species. The study concludes that Mifepristone (RU-486, 10 μg/ml) fortified semen extender maximally improves the quality and fertility of bovine frozen semen, followed by Taurine and Sericin over control, and hence addition of Mifepristone should be practiced at all semen stations for the betterment of farmers.